2007
DOI: 10.1002/chem.200700615
|View full text |Cite
|
Sign up to set email alerts
|

Alkynyl Expanded Donor–Acceptor Calixarenes: Geometry and Second‐Order Nonlinear Optical Properties

Abstract: A number of wide- and narrow-rimmed functionalized alkynylcalix[4]arenes have been synthesized by Sonogashira coupling. With respect to their optical properties, these donor-acceptor systems are treated as ensembles of covalently linked, electronically independent tolane subchromophores. Linear UV/visible and fluorescence spectroscopic investigations revealed that the charge-transfer character of the electronic transitions in calixarenes, and also the second-order nonlinear optical (NLO) properties depend on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 57 publications
7
42
0
Order By: Relevance
“…This contribution is actually identical to the one observed for any non-centrosymmetrical point-like objects such as efficient rod-like push-pull molecules. 1011, 45–46 The second contribution is multipolar contribution like electric quadrupole contribution. 12–19 This contribution is very important when the size of the particle is no longer negligible when compared to the wavelength, as we reported before.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contribution is actually identical to the one observed for any non-centrosymmetrical point-like objects such as efficient rod-like push-pull molecules. 1011, 45–46 The second contribution is multipolar contribution like electric quadrupole contribution. 12–19 This contribution is very important when the size of the particle is no longer negligible when compared to the wavelength, as we reported before.…”
Section: Resultsmentioning
confidence: 99%
“…6,8 and others 2829 have demonstrated that nanoparticle based bio-barcode assays with localized surface plasmon resonance (LSPR), are capable of measuring ADDL level in CSF. Here, we demonstrate for the first time that monoclonal ani-tau antibody (tau-mab) coated gold nanoparticle based two-photon scattering assay 1018,4647 can be used for the detection of Alzheimer’s tau protein in 1 pg/mL level which is about two orders of magnitude lower than cut-off values (195 pg/mL) for tau protein in CSF. Our results reported here demonstrate the potential for a broad application of bioconjugated nanoparticles in practical biotechnological and medical applications.…”
mentioning
confidence: 98%
“…In this sense, data has been reported in the literature concerning multichromophoric molecular systems such as calixarenes [8][9][10] and cyclotetrasiloxane rings, [11] or multilayered organized systems, where NLO molecules have be assembled by using zirconium phosphate-phosphonate (ZrPO x ) techniques, [12][13][14] layer-by-layer siloxane-based selfassembly, [15] or Langmuir-Blodgett techniques. [16] An interesting way to prepare geometrically oriented push-pull bichromophoric systems is to covalently arrange them into a highly delocalized structure with an orthogonal spatial arrangement, as in the case of 9,9Ј-spirobifluorene, where two fluorenes are connected through an sp 3 -hybridized carbon atom ( Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…A helical and close alignment of electron‐donor–electron‐acceptor entities with a large π‐conjugated backbone is of particular interest, since they can provide interchromophore dipolar interaction resulting in cooperative effects, provoking an increase in the NLO properties …”
Section: Methodsmentioning
confidence: 99%